2022
DOI: 10.3310/wbkw4927
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of an interactive quality dashboard for national clinical audit data: a realist evaluation

Abstract: Background National audits aim to reduce variations in quality by stimulating quality improvement. However, varying provider engagement with audit data means that this is not being realised. Aim The aim of the study was to develop and evaluate a quality dashboard (i.e. QualDash) to support clinical teams’ and managers’ use of national audit data. Design The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 107 publications
(208 reference statements)
0
4
0
Order By: Relevance
“…8 , 11 Realist methods have been used for studying numerous complex interventions, including health information technology (HIT), 12 and in both evaluation and design. 13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 , 11 Realist methods have been used for studying numerous complex interventions, including health information technology (HIT), 12 and in both evaluation and design. 13 …”
Section: Methodsmentioning
confidence: 99%
“… 15 In realist studies of HIT, relevant contextual factors identified have included resources, such as computing resources and support staff; users’ work routines, motivation, and confidence in HIT use; and the implementation process. 13 Realist studies start with elicitation of stakeholders’ theories. This can be done through interviewing stakeholders, reviewing existing literature, identifying theories from the sociological or other literatures, or some combination of these approaches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Ghazi Saeedi et al found alarms, drill down, and timely presentation as the central features of quality dashboards [77]. In Randell et al 's study [78], the functional requirements of quality dashboards included visualization, interaction, data quality, reporting, and notification. However, functional capabilities are used in both quality and clinical dashboards depending on the intended environment and purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Uma das táticas estratégicas, por sua vez, consiste na implementação da auditoria em saúde, uma iniciativa que teve origem no Reino Unido como resposta à necessidade premente de aprimorar a eficiência e eficácia dos serviços de saúde, eliminando práticas que se revelam ineficazes (Randell et al, 2022). Diante do contexto crescente da demanda por serviços médicos e da imperatividade de assegurar a qualidade da assistência, essa abordagem tem-se revelado de importância crucial para a otimização dos procedimentos assistenciais, garantindo, assim, a conformidade dos prontuários médicos com os protocolos estabelecidos (Dias, 2021).…”
Section: Introductionunclassified